TO THE DEBUT OF BARBORA HRÍNOVÁ UNICORNS - Buzinkaiová, Martina (Bohemica Olomucensia, 2023)
The study focuses on the debut of Barbora Hrínová Unicorns. The primary goal is to describe basic poetological parameters of short stories through interpretation and analysis. The study also deals with the literary-critical evaluation of other critics, while in the end it offers its own critical evaluation.
Keywords: Slovak literature; literary criticism; queer; unicorns; feminism; Barbora Hrínová